Turkey : Sixth and Seventh Review Under the Stand-By Arrangement; Staff Supplement; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2001)
Turkey showed good macroeconomic performance under the Stand-By Arrangement. Executive Directors stressed the need to maintain strong fiscal and monetary policies, and accelerate structural reforms. They appreciated the authority's efforts to reestablish the fiscal solvency and the adoption of the new central bank law. They agreed that the full implementation of the economic program would help restore macroeconomic stability and address the structural root causes of the country's problems, thereby laying the foundations for the resumption of growth.